The Molecular Epidemiological and Immunological Characteristics of HIV-1 CRF01_AE/B Recombinants in Nanjing, China - Ge, You; Liu, Yangyang; Fu, Gengfeng; Lu, Jing; Li, Xiaoshan; Du, Guoping; Fei, Gaoqiang; Wang, Zemin; Li, Han; Li, Wei; Wei, Pingmin (Frontiers in Microbiology, 2022)
The HIV-1 CRF01_AE/B recombinants were newly emerging strains spreading rapidly in Southern and Eastern China. This study aimed to elucidate the molecular epidemiological characteristics of HIV-1 CRF01_AE/B recombinants in Nanjing and to explore the impact of these novel strains on immunological status. A total of 1013 blood samples from newly diagnosed HIV-1 infected patients were collected in Nanjing from 2015 to 2019, among which 958 Pol sequences were sequenced successfully. We depicted the molecular epidemiological characteristics of CRF01_AE/B recombinants by molecular evolutionary analysis, Bayesian system evolution analysis and transmission network analysis. The generalized additive mixed model was applied to evaluate the CD4+ T cell count change of CRF01_AE/B recombinants. The Kaplan-Meier analysis was performed to assess the time from combined antiretroviral therapy (cART) initiation to immune reconstruction. We have identified 102 CRF01_AE/B recombinants (102/958, 10.65%) in Nanjing, including CRF67_01B (45/102, 44.12%), CRF68_01B (35/102, 34.31%) and CRF55_01B (22/102, 12.57%). According to Bayesian phylogenetic inference, CRF55_01B had a rapid decline stage during 2017 to 2019, while CRF67_01B and CRF68_01B have experienced a fast growth phase during 2014 to 2015 and then remained stable. We have constructed 83 transmission networks, in which three larger clusters were composed of CRF67_01B and CRF68_01B. CRF01_AE/B recombinants manifested faster decrease rate of CD4+ T cell count than CRF_07BC, but similar to CRF01_AE. The probability of achieving immune reconstruction in CRF01_AE/B recombinants was lower than CRF07_BC in the subgroup of baseline CD4+ T cell count less than 300 cells/μL. In summary, CRF67_01B and CRF68_01B were the major strains of CRF01_AE/B recombinants in Nanjing, which have formed large transmission clusters between Nanjing and other provinces. CRF01_AE/B recombinants might be associated rapid disease progression and poor immune reconstruction. The continuous epidemiological monitoring of CRF01_AE/B recombinants should be put more emphasis on.